PEMBATALAN PERJANJIAN KERJASAMA ANTARA WEDDING ORGANIZER DAN PENGGUNA JASA PADA MASA PANDEMI COVID-19 (STUDI PADA MELAKA WEDDING DI PEKANBARU) - Oryza Nurul Herliza; Firdaus Firdaus; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Pandemic covid-19 that hit Indonesia afect business in economy, that pandemic causingdelays in fulfillment of perfrmance. And the things that be a major problem in this finalassignment is the dispute between Melaka Wedding Organizer and the service user that happenbecause circumstance that cause by pandemic covid-19, this makes Melaka Wedding Organizercan’t do their perfrmance because obstructed by PSBB that issued by the gvernment to preventspread pandemic covid-19. The purpose of writing this final assignment is to know the causativefactor of concellation of cooperation agreement, to know how the concellation of cooperationagreement between Melaka Wedding Organizer and the service user during a pandemic covid-19.The type of study in this writing is sociological legal research, study about law thatobserve what is the characteristics of cmmunity behavior in a regon of social life. The datacollected by interview as the data source and infrmation, interview were conducted in person inthe Melaka Wedding Organizer.From the studr there are 2 major thing, first the causative factor of concellation ofcooperation agreement between Melaka Wedding Organizer and the service user during apandemic covid-19 such as pandemic, termination of employment, execution time already notright. Second, settlement form of concellation of cooperation agreement between MelakaWedding Organizer and the service user during a pandemic covid-19. The concellation ofagreement is done using good intention in accordance with chapter 1338 paragraph 3Indonesian Civil Code by deliberation the way agreement between Melaka Wedding and theservice user in chapter 5 then clarified in description section of concellation of agreementMelaka Wedding letter.Keyword: Concellation of Agreement, Wedding Organizer, Pandemic Covid-19